2008
DOI: 10.1186/1746-1448-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacillus-like organisms isolated from deep-sea hypersaline anoxic sediments

Abstract: Background: The deep-sea, hypersaline anoxic brine lakes in the Mediterranean are among the most extreme environments on earth, and in one of them, the MgCl 2 -rich Discovery basin, the presence of active microbes is equivocal. However, thriving microbial communities have been detected especially in the chemocline between deep seawater and three NaCl-rich brine lakes, l'Atalante, Bannock and Urania. By contrast, the microbiota of these brine-lake sediments remains largely unexplored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 54 publications
5
58
0
2
Order By: Relevance
“…30% along the transition from the upper to the lower halocline in Discovery (Figure 4). Moreover, OTU1288 is very closely associated (Table S3) to a Clostridium--like phylotype, found previously in the L'Atalante basin (Sass et al 2008). These observations suggest that these two OTUs may represent potentially active populations in the halocline sediments.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…30% along the transition from the upper to the lower halocline in Discovery (Figure 4). Moreover, OTU1288 is very closely associated (Table S3) to a Clostridium--like phylotype, found previously in the L'Atalante basin (Sass et al 2008). These observations suggest that these two OTUs may represent potentially active populations in the halocline sediments.…”
Section: Methodssupporting
confidence: 72%
“…the Burkholderiales, but are mostly associated with soils. Representatives of some bacteria not frequently found in typical marine environments that have been found in other DHAB waters include sequences affiliated with the genus Bacillus from the Urania chemocline and brine water column (Sass et al 2008). Surface sediments underlying DHAB brines, at least in terms of water activity and water potential (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the methylamine degradation pathway in the genus Bacillus is poorly characterized, all Gram-positive methylotrophs studied to date use the methylamine oxidase pathway (Chistoserdova et al, 2009). Methylamine SIP sequences from our study clustered with the 16S rRNA gene sequences of both methylotrophic Bacillus strains (Arfman et al, 1992;Anesti et al, 2005) and strains isolated from contaminated soils (Desai et al, 2009;Stobdan et al, unpublished) and marine sediments (Dick et al, 2006;Sass et al, 2008) (Figure 3). This is the first SIP study to identify methylamine-utilizing Bacillus spp.…”
Section: Discussionmentioning
confidence: 80%
“…Ba cil lus spe cies, iden ti fied in this study, were reported to be wide spread in sa line wa ters. B. pumilus and B. licheniformis were iso lated from sea wa ter of dif fer ent ar eas of the Pa cific Ocean (Ivanova et al, 1999), as well as from deep ocean sed i ments (Ettoumi et al, 2009) and deep sea, hypersaline anoxic brine lakes (Sass et al, 2008). Many Ba cillus spe cies, in clud ing B. licheniformis and B. methylotrophicus, were iden ti fied among halophilic and halotolerant iso lates retrieved from the brines of Karak Salt Mines in Pa ki stan.…”
Section: A1 Wetlands 99mentioning
confidence: 99%